Schools of Democracy. (December 2019) - Sinyai, Clayton
In the late 20th century, a wave of democratic transformation swept away dictatorships of the right and left across Europe, Africa and much of Asia; and for the first time in human history most citizens lived under governments they had chosen in free elections. Liberal democracy, characterized by multiparty elections, individual liberties, free enterprise and independent trade unions, seemed poised to dominate the future, but today populist movements challenge the liberal consensus and global public opinion surveys indicate a loss of faith in democratic values. The rapid decline in labor union membership across the developed world may be a contributing factor. Social scientists have documented the function of labor unions as "schools" of democracy where working-class high school graduates learn crucial civic skills, boosting their political participation and reducing the gap between socioeconomic classes. This may explain why AFL President Samuel Gompers's observation, that "there never yet existed coincident with each other autocracy in the shop and democracy in political life" remains true 125 years later, and highlights a major threat to democracy today.